Meningkatkan Literasi Siswa di SMPN 2 Ambulu dengan Memanfaatkan Perpustakaan Digital Let’s Read melalui Program Kampus Mengajar 7 - Anindya Oktaviona Ervinawati; Astri Widyaruli Anggareni (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
One of the learning activities that can improve the quality of student learning is to provide a variety of teaching methods and learning media that can engage students' enthusiasm during the learning process. Based on the results of reading literacy tests, Indonesia has not yet reached the standard score of 493 set by the OECD. Literacy is very important for daily life, therefore the Ministry of Education in Indonesia provides opportunities for students to develop their creativity in improving literacy, numeracy, and the quality of learning in schools. Students assist educators in varying teaching methods or media to make learning active, interactive, and enjoyable. One enjoyable learning media is utilizing technology, such as the Let's Read digital library. This research uses a qualitative research method with a case study research design, and the techniques used in this research include observation, practice, and direct documentation in teaching activities in the classroom using the Let's Read media.